An Unusual Bifid Piriformis Muscle with High Division of Sciatic Nerve - Goshi , Rashmi C. (Current Practice in Medical Science Vol. 7, 2022)
The sciatic Nerve can rarely be separated into tibial and common fibular Nerve within the Pelvis. In these circumstances, the common fibular nerve and tibial nerve exit the pelvis in distinct ways. This Objectives of this study is to know the variation in piriformis muscle and division of sciatic nerve. The variant discovered by MBBS students during normal dissection of a 30-year-old male cadaver at the JJM Medical College in Davangere, Karnataka, India. The difference is On the right side of a 30-year-old male cadaver, there is a high division of the sciatic nerve. The bifid piriformis's two divisions are where the common peroneal nerve is situated, whereas the tibial nerve runs beneath the inferior piriformis. Understanding this variance is crucial for treating sciatic nerve entrapment that causes nondiscogenic sciatica, and it also necessitates a review of the piriformis syndrome.